Rekonstruksi Manajemen Tata Kelola Wakaf Melalui Pengembangan Nadzir Profesional Di Kabupaten Bulukumba (AT TAWAZUN: Jurnal Ekonomi Islam, 2023)
This study aims to determine the management of waqf management and professional nazir development in Bulukumba Regency. The method used in this study is descriptive qualitative using a phenomenological approach, with primary and secondary data sources. To test the validity of the data, researchers used triangulation of sources by collecting data, reducing data, presenting data and drawing conclusions. The results of this study indicate that the implementation of POAC management in waqf management by nadzirs is still traditional and only limited to religious activities. In addition, there are nadzirs who are not yet professional, so that waqf cannot be managed optimally. The development of professional nadzirs in Bulukumba Regency is currently still in the process of being reformed, this is indicated by the formation of the nadzir forum organization and the Indonesian Waqf Board. In addition, several excellent programs have been established that can assist the development of waqf. Therefore, it is necessary to improve the management of waqf assets through more professional nadzirs so that the function of waqf as an instrument of economic development can be achieved.